Efficacy and safety of once-weekly semaglutide for the treatment of type 2 diabetes: Protocol for a systematic review and meta-analysis. Issue 16 (April 2018) - Shi, Fang-Hong; Li, Hao; Cui, Min; Zhang, Zai-Li; Gu, Zhi-Chun; Liu, Xiao-Yan
Abstract: Background: It is a great challenge for type 2 diabetes mellitus (T2DM) patients to maintain optimal glycemia, control body weight, blood pressure, and avoiding hypoglycemia. Glucagon-like peptide-1 (GLP-1) receptor agonists (GLP-1 RAs) can stimulate glucose-dependent insulin while inhibit glucagon secretion, delay gastric emptying, reduce appetite, and energy intake. Recently, a new once-weekly GLP-1 RAs, semaglutide, has been registered to treat patients with T2DM. Methods: We will search Medline, Embase, Cochrane Library, and the ClinicalTrials.gov Website up to February 2018. Studies will be screened by title, abstract, and full text independently in duplicate. Phase III randomized controlled trials (RCTs) reports efficacy and safety data of semaglutide will be eligible for inclusion. Outcome variables will be assessed included glycemic control indexes (glycosylated hemoglobin [HbA1c]%, fasting plasma glucose [FPG], self-monitoring of blood glucose [SMPG], postprandial self-monitoring of blood glucose [PSMPG]), blood pressure indexes (systolic blood pressure [SBP], diastolic blood pressure [DBP], and pulse rate), body weight control indexes (body weight, body mass index [BMI], and waist circumference), and any adverse events (including adverse events [AEs] varying degrees and AEs occurring in ≥5% patients by preferred term or other of clinical interest). Assessment of risk of bias and data synthesis will be performed using STATA software (version 12, Statacorp, College Station, Texas). Outcomes will report by weight mean difference (WMD) and risk ratios (RRs) and their 95% confidence intervals (95% CIs). Heterogeneity among studies will be evaluated using the I 2 statistic. Results: This review will evaluate glycemic, blood pressure, body weight control, and any adverse events of semaglutide as compared with other therapies. Conclusion: Our study will provide a comprehensive picture of semaglutide in T2DM.